3, 4-Dihydroxybenzaldehyde quenches ROS and RNS and protects human blood cells from Cr(VI)-induced cytotoxicity and genotoxicity. (August 2018) - Husain, Nazim; Mahmood, Riaz
Abstract: Hexavalent chromium [Cr(VI)] is the most toxic and potent form of chromium and induces multiple organ damage in humans and experimental animals. Oxidative stress has been implicated in the toxicity of Cr(VI). We have examined the potential role of 3, 4-dihydroxybenzaldehyde (DHB), a plant polyphenolic antioxidant, in protecting human erythrocytes and lymphocytes from Cr(VI)-induced cytotoxicity and genotoxicity. Erythrocytes were treated with potassium dichromate, a Cr(VI) compound, in presence and absence of DHB. Incubation of erythrocytes with Cr(VI) enhanced the generation of reactive oxygen and nitrogen species, increased lipid and protein oxidation, methemoglobin levels, and lowered antioxidant power of cells. However, prior treatment of erythrocytes with DHB, resulted in a significant DHB dose-dependent decrease in reactive oxygen and nitrogen species levels and restoration of oxidative stress parameters. DHB also improved the antioxidant power of erythrocytes and restored the activities of major antioxidant, metabolic and membrane bound enzymes. Electron microscopic studies images DHB prevented Cr(VI)-induced morphological changes in erythrocytes. The single cell gel electrophoresis assay showed that DHB mitigated Cr(VI)-induced DNA damage in lymphocytes. These results clearly show that DHB protects human blood cells from Cr(VI)-induced oxidative damage and can be potentially used in reducing the toxic effects of this metal ion. Highlights: Cr(VI) induces oxidative stress in human blood cells. 3, 4-dihydroxybenzaldehyde effectively quenches ROS and RNS generation. DHB prevented Cr(VI)-induced cytotoxicity and genotoxicity.